Data Clustering Technique for In-Network Data Reduction in Wireless Sensor Network - Alam, M.K. (Institute of Electrical and Electronics Engineers Inc., 2019)
In wireless sensor networks (WSNs), plenty of sensor nodes are typically deployed in the field to provide a long-term monitoring facility. These sensor nodes are usually collect a huge amount of data over time. Transmitting the huge data from the sensor nodes to a sink introduces a big challenge to the network due to energy constraint of the sensor nodes. Therefore, many research efforts have been carried out so far to design efficient data clustering techniques for WSNs. The main purpose of these techniques is to reduce the amount of data over the network while retaining their fundamental properties. This paper aims to develop a Histogram-based Data Clustering (HDC) technique at the cluster-head (CH) for in-network data reduction. The HDC groups the homogeneous data into clusters and then performs in-network data reduction by selecting the central values (instead of all data points) of each cluster. Simulations on real-world sensor data show that the proposed HDC can effectively reduce a significant amount of redundant data and outperform existing techniques. Â© 2019 IEEE.